2004
DOI: 10.1111/j.1365-2923.2004.01735.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching research methodology in medical schools: students' attitudes towards and knowledge about science

Abstract: Medical students have generally positive attitudes towards science and scientific research in medicine. Attendance of a course on research methodology is related to a positive attitude towards science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
154
4
19

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 181 publications
(192 citation statements)
references
References 12 publications
9
154
4
19
Order By: Relevance
“…Another study reported a progressively larger fraction of medical students and graduates who expressed serious interest in research careers [6]. Our research group showed that teaching research methodology is associated with increase in positive attitudes towards science among medical students [8], and that among family medicine practitioners there was a positive association between attitude toward science and opinion of research methodology training as a mandatory part of the medical curriculum [9].…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…Another study reported a progressively larger fraction of medical students and graduates who expressed serious interest in research careers [6]. Our research group showed that teaching research methodology is associated with increase in positive attitudes towards science among medical students [8], and that among family medicine practitioners there was a positive association between attitude toward science and opinion of research methodology training as a mandatory part of the medical curriculum [9].…”
Section: Introductionmentioning
confidence: 51%
“…The findings of our study may have important implications for developing strategies for recruiting new generations of academic physicians, as fostering positive attitudes toward science among medical students seems not only achievable [8] but also related to the intrinsic motivation, a key factor for a long-term engagement in research [24]. One of the methods to cultivate positive attitudes towards science is mentoring, which was proven to be effective among the young people [26], and was also reported to have an important influence on career choice and research productivity in the context of academic medicine [27].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations